Direct photopatterning of BODIPY-based small Molecules via thiol-ene click chemistry - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2022)
© 2022 Wiley-VCH GmbH.We demonstrate a BODIPY-based small molecule photopatterned surface by thiol-ene click chemistry at room temperature utilizing only 366 nm UV light. The resulting cross-linked polymer exhibits porous surfaces according to AFM and TEM results. A dramatic blue shift occurred in absorption spectra and the photoluminescence was also intensified as a result of crosslinking. Optical and electrochemical results are compatible with the DFT calculations. The obtained results prove that the photopatterned BODIPY-based material can be easily and inexpensively applied in multilayer optoelectronic devices.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; ENERJİ VE YAKITLAR; MALZEME BİLİMİ, BİYOMATERYAL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENERGY & FUELS; MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Biyomalzemeler; Fizik Bilimleri; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Enerji Mühendisliği ve Güç Teknolojisi; Malzeme Kimyası; Biomaterials; Physical Sciences; Renewable Energy, Sustainability and the Environment; Energy Engineering and Power Technology; Materials Chemistry; BODIPY; electrochemistry; photopatterning; surface characterization; thiol-ene click